Zero-Tolerance Comes to International Law. (2015) - Gruber, Aya
Abstract : It is difficult to engage from a theoretical perspective an advocacy piece that largely reads like a brief in favor of particular claim of law, namely, that a state's failure to (vigorously) criminalize marital rape violates international human rights law. In a brief, the litigant pulls together various sources to prove the legal claim is correct. Opponents typically respond by cobbling together their own sources to undermine that claim. In their essay, Criminalizing Sexual Violence Against Women in Intimate Relationships, Randall and Venkatesh set out to prove that international human rights law, in fact, requires states to criminalize marital rape. I suspect there are international lawyers who can persuasively argue that international human rights law does not, in fact, require such criminalization.